Relationships between earthquakes, hurricanes, and landslides in Costa Rica - Quesada Román, Adolfo (2019)
Landslides are a common natural hazard in Costa Rica, recurrently triggered by seismicity and extraordinary rainfall. Here, we investigate the coalescence of both processes and their ability to trigger massive landslides and debris flows in Costa Rica. The study focuses on Miravalles Volcano, affected by an earthquake of 5.4 Mw on July 2, 2016, and by intense rainfalls related to Hurricane Otto only 4 months later, on November 24, 2016. During the passage of Hurricane Otto, ~300 mm of rain were recorded in the study region. We use logistic general linear regression models (GLM) to represent the statistical relationships between the factors controlling landslides (such as epicenter distance, rainfall during Hurricane Otto, altitude, and slope). The compound 2016 event triggered 942 landslides, of which 62% were located within 3–6 km from the Bijagua earthquake epicenter, and on the eastern, southeastern, and southern slopes of Miravalles Volcano, i.e., in the zone where the density of local faults is highest and rainfall reached maximal values during the hurricane. The statistical analysis supports the existence of coupled earthquake-hurricane dynamics with higher landslide densities close to the epicenter and at sites receiving larger rainfall totals, but also showing higher slopes and altitudes. Debris flows affected an area of ~27 km2 and moved down the river systems, leaving eight casualties around the volcano and ca. 103 million US$ of losses in Upala and Bagaces. Results of this study can be useful for the assessment and understanding of geological and hydrometeorological hazards in Costa Rica and other tropical countries.